Atividades diárias e percepção de Barreiras e Facilitadores para Prática de Atividade Física de Pessoas com Déficit Intelectual - Jung, Laura Garcia (2013)
In the last years, the new lifestyle conditions have determined sedentary behaviors, which in turn in increase the risk of non-communicable diseases. Regarding the individuals with intellectual deficit, this situation is even more risky because studies show that physical activity level of these individuals is lower as compared to the population. The purpose of this study is to describe the perceptions of family members of children with intellectual deficit aged 6 or more enrolled in the APAES of the Rio Grande do Sul regarding the barriers and facilitators for leisure-time physical activity of their offspring. A no probabilistic, intentional sample was selected. The APAES were contacted and data collection were delivered and handled back through the mail. A sample of 1191 individuals with intellectual deficit represented by their parents took part in the study. In terms of personal aspects, the main barriers for physical activity are related to lack of money and motivation preference for other activities than not physical activities. Regarding the environmental aspects, the main barrier is the absence of social projects near the individual‟s place. Family members responsible for individuals between 20 and 30 perceived the existence of places near their place; however they reported that these places are not accessible for individuals with intellectual deficit. Regarding the social aspects, lack of company is the main barrier for physical activity practice. It was concluded that some barriers and facilitators are linked to the stimulus that people with intellectual deficit receive. This stimulus might evoke the pleasure for physical activity practice and having a company of somebody is an important support due to the lack of independence and autonomy.Financial aspects also influence physical activity practice, which shall be minimized by public policies and social projects aimed to give opportunity to these individuals to practice some physical activity and, through an active lifestyle, achieve a greater quality of life